The Rights and Duties of Spouses: A Study Based on the Qur’an and Indonesian Marriage Law - Delvi Slaras Hati; Elen Desta Sari (Universitas Sultan Ageng Tirtayasa, 2025)
This study discusses the rights and obligations of husband and wife from the perspective of the Qur'an and Indonesia’s Marriage Law. The background lies in the gap between understanding and practice of marital roles, especially when religious values interact with state law. The purpose is to analyze the compatibility and divergence between Qur'anic norms and the provisions of Law No. 1 of 1974 on Marriage. This research employs a qualitative normative-comparative method, analyzing relevant Qur'anic verses and comparing them with legal statutes. The findings show a general harmony between the Qur'an and the Marriage Law in regulating balanced roles, such as financial responsibility, mutual respect, and cooperation in family life. However, interpretive and practical differences remain, posing challenges for family law implementation in Indonesia. This research contributes to Islamic legal literature and provides insights for policymakers to align national law with religious values.